2021
DOI: 10.1186/s12302-021-00490-2
|View full text |Cite
|
Sign up to set email alerts
|

Natural attenuation along subsurface flow paths based on modeling and monitoring of a pesticide metabolite from three case studies

Abstract: Background Groundwater—especially for the use as drinking water—is a strictly protected resource in the existing guidelines for pesticide registration and drinking water protection in the EU. One aspect that has hardly played a role in this context so far is the attenuation of pesticide concentrations along the flow path from the regulatory leaching concentration at a depth of 1 m below the applied field to raw water abstraction systems. The soil metabolite N,N-dimethylsulfamide (DMS) is formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Processes that result in lower concentrations are for example hydrodynamic dispersion, diffusion and degradation in the saturated zone (Tiktak et al., 2005 ). Herrmann and Sur ( 2021 ) demonstrated that the concentration of the metabolite N,N‐dimethylsulfamide (DMS) decreased continuously and consistently when the substance was followed from its formation in soil below a treated field, to its leaching into the aquifer, and within the aquifer down to the raw water collection site. Preferential flow is one of the known processes that could make the assessment at Tier‐4 more conservative.…”
Section: Principle Of the Tiered Approach And Challenges For The Grou...mentioning
confidence: 99%
“…Processes that result in lower concentrations are for example hydrodynamic dispersion, diffusion and degradation in the saturated zone (Tiktak et al., 2005 ). Herrmann and Sur ( 2021 ) demonstrated that the concentration of the metabolite N,N‐dimethylsulfamide (DMS) decreased continuously and consistently when the substance was followed from its formation in soil below a treated field, to its leaching into the aquifer, and within the aquifer down to the raw water collection site. Preferential flow is one of the known processes that could make the assessment at Tier‐4 more conservative.…”
Section: Principle Of the Tiered Approach And Challenges For The Grou...mentioning
confidence: 99%
“…The surface water compartment serves as a first example of concept and methodology. In principle, the concept can be transferred to groundwater as well, i.e., starting with regulatory PEC gw values and consideration of dilution factors until the point of abstraction [29] by additionally taking geometric configuration of groundwater aquifers into account.…”
Section: A Proposal For a Stepwise Exposure Assessment For The Eumentioning
confidence: 99%
“…The surface water compartment serves as a rst example of concept and methodology. In principle, the concept can be transferred to groundwater as well, i.e., starting with regulatory PEC gw values and consideration of dilution factors until the point of abstraction [29] by additionally taking geometric con guration of groundwater aquifers into account.…”
Section: A Proposal For a Stepwise Exposure Assessment For The Eumentioning
confidence: 99%